PENGARUH MULTIMEDIA TERHADAP HASIL BELAJAR SISWA PADA KONSEP BANGUN RUANG DI KELAS V SEKOLAH DASAR (Studi PreEksperimen terhadapPembelajaranMatematika diKelas V SD di Kecamatan Cihideung Kota Tasikmalaya) - ANDRIYANTO, Taufik (2014)
This research was motivated by the lack of media use by teachers in mathematics, so the atmosphere of learning in math tendwith boredom on students. Multimedia learning is regarded as an attractive media based efforts touched various senses (sight, hearing, and touch). Likewise in mathematics instructional media tends to determine the potential improvement of student learning.This research usedpre experiment with populations fifth grade Elementary School students in District 2 CihideungCieunteungTasikmalaya, amounting to 29 students. The instrument used the pretest and posttest on the material geometrical concepts. The objectives of this research are: (1) To determine student learning outcomes in mathematics about geometrical concepts using multimedia, (2) To determine the effect of the use of multimedia in learning to student learning outcomes in mathematics learning about geometrical concepts. The results showed that: (1) an average of the results of student learning about geometrical concepts in learning determines the geometrical volume of cubes and blocks views of the pretest scores fall into the high category with a percentage of 59.86%; (2) the average of the student learning outcomes in learning geometrical concepts determine the geometrical volume of cubes and blocks views of the post-test scores fall into the category of very high with the percentage reached 72%; (3) The use of learning by using multimedia affecting student learning outcomes of students in mathematics learning about geometrical concepts. This is evidenced by the acquisition of the average percentage value of greater than pretest posttest. Regarding the acquisition of the t test 7,995 sig.The value based on probability (Sig <0.05), it can be concluded that Hi rejected and Ho accepted. This evidenced the strong correlation coefficient interpretation. Thus, the effect of learning by using multimedia to the student learning outcomes of students including to the strong criteria. Keywords:Multimedia, Student Learning Outcomes, Build Space Concept